Dinamika Relasi Kuasa dan Komunikasi Digital dalam Praktik TikTok Affiliate sebagai Bentuk Digital Labor - Nugrahanti, Erma Diah Putri; Widyasari, Wulan (Jurnal Audiens, 2026)
Digital transformation has generated new forms of work that are often unrecognized as labor in the conventional sense, one of which is digital labor. The TikTok Affiliate program in Indonesia represents a concrete example of how content production, product promotion, and algorithm-driven monetization are integrated within a single platform-based economic ecosystem. This study aims to analyze how power relations operate within the TikTok Affiliate program from the perspective of affiliates as potentially exploited digital laborers. Specifically, the research examines mechanisms of algorithmic control, processes of value production, and how affiliates perceive and experience their position within the platform’s work structure. This study employs a qualitative approach using phenomenological methods, with in-depth interviews conducted with beginner affiliates participating in a TikTok Affiliate community. The findings reveal that power relations are exercised through opaque algorithmic control, fluctuating commission systems, and visibility distribution fully governed by the platform. Value production extends beyond product sales to include the accumulation of data, engagement, and attention that strengthen the platform’s capital accumulation. However, many affiliates do not necessarily perceive their condition as exploitation, but rather as a flexible economic opportunity. This indicates the internalization of algorithmic norms that shape self-disciplining digital labor practices. The study concludes that the TikTok Affiliate program represents a new form of digital labor exploitation within platform capitalism, where creative work is framed as entrepreneurship while remaining embedded in asymmetric power relations.